The Standard Operating Procedures in COVID-19 Pandemic for Periodontal Aerosol-Generating Procedures: A Process Audit - Haseeb, Muhammad; Khalid, Naima; Syed, Azeem Ul Yaqin; Khan, Zubair Ahmed; Qureshi, Farheen; Ahsen, Iftikhar (European Journal of Dentistry, 2022)
Objective This study aims to audit the process of patient management with aerosol-generating procedure (ultrasonic scaling) while adherence to the guidelines for health care workers (HCWs) during the coronavirus disease 2019 (COVID-19).Materials and Methods Audits records at the Department of Periodontology at University College of Medicine and Dentistry Hospital, Lahore, Pakistan were collected (prospectively) over the period of October 1 to November 30, 2020 (1st cycle) and December 14, 2020 to February 12, 2021 (2nd cycle). The audit was divided into three components based on the guidelines: (1) physical environment, (2) patients/appointments, and (3) COVID standard operating procedures related to HCWs.Results The recommended physical layout and procedural factors, as suggested by the guidelines for dental clinics, were observed during the first cycle of audit, and discrepancy of ventilation system was fixed after the first cycle. Audit team reported the observance of fallow time three times daily, which revealed 83.3% observance of fallow time.Later in the second cycle when the extraoral high-volume air evacuator was installed, the fallow time was reduced to 15 minutes and not only five procedural slots per day were created but fallow time was also observed 100% of the time.Conclusion Following the standard guidelines resulted in more efficient working environment and lesser risk for HCWs while performing aerosol-generating procedures.
Keywords: aerosol-generating procedures; clinical audit; COVID-19; standard operating procedures; ultrasonic scaling